A Critique of Earthquake Policies of Northern Cyprus - Hurol, Yonca; Wilkinson, Nicholas (ICE Institution of Civil Engineers, 2005)
The same building codes and specifications have been used in Turkey and Northern Cyprus for more than thirty years. Similarly, the most preferred technologies are the same in both countries. One of the most frequently used building technologies is that of the reinforced concrete frame system with non-load bearing brick walls. However, when earthquakes occur in Turkey, this system frequently causes serious structural problems, culminating in building collapse and a huge loss of human life. Building codes, including those of Turkey and Northern Cyprus, usually include solutions to these problems, which can only be carried out by structural engineers, but which ignore the existence of other possible solutions, which may also be carried out by architects. The research objective of this paper is: 1. To carry out a preliminary investigation into the existence of the same or similar problems in Northern Cyprus, but not in the southern part of the island. 2. To identfy and propose a more appropriate strategy to combat and resolve the problem. Similar research and strategies will be very important for the country in the process of unification with the European Union. For this purpose, only the “soft storey” and “short column” problems are studied as cases demonstrating evidence of the severity of the problem. With the help of a comparative research carried out in the town of Famagusta, in Northern Cyprus, the paper defines the problems, outlines the solutions to them, and compares these solutions with those defined in the building codes and specifications of other nation states. Ultimately, it is shown that: - It is worth carrying out a more detailed research into the degree of the earthquake resistance of the reinforced concrete buildings in Northern Cyprus. - It is better to propose multiplicity of solutions which will connect all the related professions in the common aim of developing a social strategy, which will combat earthquakes, if it is understood that a singular hypothesis is not in any way sufficient or adequate to solve the problem as it currently exists in Turkey to-day.
The aim of this article is to demonstrate the earthquake problems that exist in North Cyprus and to criticize the building code which is applied.
Keywords: earthquake policy, reinforced concrete frame, architecture, safety